"The Africanization of Pop music in the United States: Alex Boye's cultural claims as a Latter- Day Saint on Youtube". - (:unkn) unknown (My University, 2018)
The Church of Jesus- Christ of Latter- day Saints has always been seen as a "white church" throughout history. Yet, one of its most weel- known singers is Alex Boye, an African - American from Kenyan origins. He has voluntarily accepted to be put forward by his church to both deny any existence of racist doctrines in his religion, and to reach a wider public that would enjoy the African rythms in his music. This article is an analysis of the context behind his success on Youtube.
Keywords: African Research